Materials science and applied chemistry selected, peer reviewed papers from the 58th International Conference of Materials Science and Applied Chemistry--MSAC 2017, October 20, 2017, Riga, Latvia - Kokars, Valdis (Key engineering materials, 2018)
The special edition of the journal "Key Engineering Materials" contains papers that were presented to the 58th International Conference of Materials Science and Applied Chemistry (MSAC 2017, 20th October, 2017, Riga, Latvia). The main objective of this collection is to present the latest scientific findings obtained in the fields of materials science and chemistry.